Gender variance in the Deployment of ICTs by library and Information Science students in Universities in Southern Nigeria - Arumuru, Lawrence; Toyo, oghenevwogaga David (Daluang: Journal of Library and Information Science, 2025)
Purpose. The Research examined the gender variance in the deployment of ICTs by library and information science students in the library schools in southern Nigeria. The research addressed four research queries and formulated hypotheses. Methodology. The research design deployed in the research was descriptive. A structured questionnaire was deployed as a data collection tool. The research population included 6,247 LIS students from 12 library schools in southern Nigeria. The sample consisted of 624 respondents selected using standard random sampling methods. The data collected were analysed using mean, standard deviation, percentage and product-person-moment correlation coefficient (PPMC). Results and Discussion. The research showed that ICT tools are easily accessible for university students. Accessibility was found to have a momentous impact on the deployment of ICT among LIS students in southern Nigerian universities. Conclusion. The study concludes that while both male and female LIS students in Southern Nigerian universities actively use ICT tools with equal frequency, their limited proficiency and tendency to prioritise non-academic use highlight the need for targeted educational initiatives to enhance productive and skilful ICT deployment. Based on the research results, it was recommended that ICT training courses and workshops be provided for LIS students to improve their expertise in using these tools.